Selection and evaluation of software. - ROWLEY, J.E. (1993)
Advises that software selection must be guided by appropriate criteria such as cost, lifetime and life history, originator, supplier, support, maintenance, technical considerations, and compatibility, ease of use, interfaces and integration. Presents a checklist for the evaulation of database software.